Exercise physiology - Green, Jorge (Larsen & Keller, 2017)
This book is a compilation of chapters that discuss the most vital concepts in the field of exercise physiology. It provides deep insights about the fundamentals of this area. Exercise physiology refers to the study of the effects and results of different exercises. It examines the effect exercise has on humans like the various metabolic changes happening in the brain and other body parts, fatigue and its effects on brain. This textbook unfolds the innovative aspects of exercise physiology that will be crucial for the holistic understanding of the subject matter. Coherent flow of topics, student-friendly language and extensive use of examples make this text an invaluable source of knowledge.--Back cover